Development of Thermoelectric Generator for Automotive Current Generation System - Abdul Rahim, Muhammad Syafiq; Ibrahim, Md Zin (Progress in Engineering Application and Technology, 2023)
The aim of this project is to develop and study the potential of renewable energy source through heat waste recovery by the application of thermoelectric generator (TEG). TEG system offers direct conversion of energy from heat waste into electrical powers. Main objectives are to obtain fundamental theory and characteristic of thermoelectric in automotive system, evaluating thermoelectric generator compatible for powering up automotive electrical system and also to develop an alternative to alternator function for commercial value. The model of thermoelectric generator system is designed in Solidworks and Ansys Workbench is used for simulation purpose. Parameters involved in this project are temperature input, temperature at thermoelectric generator module hot side, temperature at thermoelectric generator module cold side, temperature difference, voltage output, seebeck coefficient and thermoelectric generator efficiency. Minimum and maximum input temperature is 100℃ and 325℃ respectively. Results of this simulation is focused on voltage generation with efficiency achieved as key findings. Lowest voltage produced from the simulation is 3.50V at 4.29℃ of temperature difference and highest voltage generated is 9.72V at 93.43℃ of temperature difference. Lowest recorded efficiency is 1.10% and highest efficiency is 6.07%, giving a 4.97% difference between lowest and highest efficiency value. This study can help future researchers to improve development of thermoelectricity in automotive applications.